2022
DOI: 10.1039/d1ob02441h
|View full text |Cite
|
Sign up to set email alerts
|

Convergent access to mono-fluoroalkene-based peptidomimetics

Abstract: The convergent and selective preparation of (Z)-monofluoroalkene-based dipeptide isosteres from functionalized fluorosulfones as cornerstone is described. In this approach, the N-terminal amino group is introduced by a conjugate addition reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For this purpose, sulfone 9 was reacted with aldehydes 173 under LiCl and NEt 3 in THF. 117 Fluorovinylsulfone compounds 174 were synthesized in the form of Z / E isomers (ratio from 42 : 58 to 99 : 1). In the case of derivatives containing alanine, serine, and lysine in their structure, good to very good yields were observed, but only moderate Z / E selectivity.…”
Section: Application Of 1-fluoro-1-arylsulfonyl Methanephosphonate De...mentioning
confidence: 99%
“…For this purpose, sulfone 9 was reacted with aldehydes 173 under LiCl and NEt 3 in THF. 117 Fluorovinylsulfone compounds 174 were synthesized in the form of Z / E isomers (ratio from 42 : 58 to 99 : 1). In the case of derivatives containing alanine, serine, and lysine in their structure, good to very good yields were observed, but only moderate Z / E selectivity.…”
Section: Application Of 1-fluoro-1-arylsulfonyl Methanephosphonate De...mentioning
confidence: 99%
“…Enriching the variety of the above described α ‐amino‐monofluoroalkenes, the group of Pfund and Lequeux [73] described a convergent and selective preparation of Z ‐monofluoroalkene‐based dipeptide isosteres from functionalized fluorosulfones using the Julia‐Kocienski olefination (Scheme 33). The reactivity of sulfones 177 was initially evaluated in a model reaction with benzaldehyde or p ‐bromobenzaldehyde where it was found that phthalimido‐sulfone 177 a gave the best results regarding yield and Z ‐selectivity.…”
Section: Synthesis Of Trisubstituted Alkenes Via Julia‐kocienski Olef...mentioning
confidence: 99%